The Immunoglobulin Superfamily Member Basigin Is Required for Complex Dendrite Formation in Drosophila - Shrestha, Brikha R.; Burgos, Anita; Grueber, Wesley B. (Frontiers in Cellular Neuroscience, 2021)
Coordination of dendrite growth with changes in the surrounding substrate occurs widely in the nervous system and is vital for establishing and maintaining neural circuits. However, the molecular basis of this important developmental process remains poorly understood. To identify potential mediators of neuron-substrate interactions important for dendrite morphogenesis, we undertook an expression pattern-based screen in Drosophila larvae, which revealed many proteins with expression in dendritic arborization (da) sensory neurons and in neurons and their epidermal substrate. We found that reporters for Basigin, a cell surface molecule of the immunoglobulin (Ig) superfamily previously implicated in cell-cell and cell-substrate interactions, are expressed in da sensory neurons and epidermis. Loss of Basigin in da neurons led to defects in morphogenesis of the complex dendrites of class IV da neurons. Classes of sensory neurons with simpler branching patterns were unaffected by loss of Basigin. Structure-function analyses showed that a juxtamembrane KRR motif is critical for this function. Furthermore, knock down of Basigin in the epidermis led to defects in dendrite elaboration of class IV neurons, suggesting a non-autonomous role. Together, our findings support a role for Basigin in complex dendrite morphogenesis and interactions between dendrites and the adjacent epidermis.